PRE-MARITAL GUIDANCE IN BUILDING A SAKINAH FAMILY AT THE GANDING SUB-DISTRICT REGILIOUS AFFAIRS OFFICE - siti Khotijah; Linatul Anisyah; Anni Annisa (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2023)
Premarital guidance is program which is very important for potential partner to use equib knowledge inorder tobuild a goog family. As the purpose of premarital guidance is to help prospective couples to build a strong family toward the creation of a sakinah, mawaddah, warahmah family. However, many couple comment that the premarital guidance in only a formality, and only fulfills the marriage reguirements. Which ultimately has an impact on the lack of harmony in the household, as well as an increase in the divorce rate. So thatteh focus of the problem in this research is how to implement premarital guidance and what is the impact of implementing premarital guidance in the KUA of Ganding sub-district. Research using a qualitative research approach to the type of descriptive study. Data collection techniques used are interviews, observation, and ducomentation. The results of this study indicate the implementation of premarital giuidance in building a sakinah family at the Ganding sub-district religious affairs office in 2022, namely setting a catin, procedures and administration, and following premarital guidance material. And this research shows the impact of implementing premarital guidance in building a sakinahfamily in the religious affairsoffice of Ganding sub-districtin 2022.Keywords: Premarital, guidance, sakinah family